2021
DOI: 10.1017/s204017442100060x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Health and Disease, resilience and social justice in the COVID era

Abstract: The COVID-19 pandemic has shone a spotlight on how health outcomes are unequally distributed among different population groups, with disadvantaged communities and individuals being disproportionality affected in terms of infection, morbidity and mortality, as well as vaccine access. Recently, there has been considerable debate about how social disadvantage and inequality intersect with developmental processes to result in a heightened susceptibility to environmental stressors, economic shocks and large-scale h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For instance, global vaccine coverage declined between 2020 and 2021, with 25 million children missing out on essential vaccines due to pandemic‐related disruptions 11 . The field of Developmental Origins of Health and Disease (DOHaD) has shown that both gender and socio‐economic inequalities not only affect maternal health and well‐being but can also have an intergenerational effect long term 12 . Using a social justice lens to uncover health disparities and the impact on MNCAH post‐pandemic is key to developing policies and interventions that look beyond health systems to include wider factors like the environment, poverty, gender and ethnicity that affect health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, global vaccine coverage declined between 2020 and 2021, with 25 million children missing out on essential vaccines due to pandemic‐related disruptions 11 . The field of Developmental Origins of Health and Disease (DOHaD) has shown that both gender and socio‐economic inequalities not only affect maternal health and well‐being but can also have an intergenerational effect long term 12 . Using a social justice lens to uncover health disparities and the impact on MNCAH post‐pandemic is key to developing policies and interventions that look beyond health systems to include wider factors like the environment, poverty, gender and ethnicity that affect health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11 The field of Developmental Origins of Health and Disease (DOHaD) has shown that both gender and socio-economic inequalities not only affect maternal health and well-being but can also have an intergenerational effect long term. 12 Using a social justice lens to uncover health disparities and the impact on MNCAH…”
Section: Key Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unraveling the molecular mechanisms underlying the pathogenesis of NDDs is important because there are no therapeutic drugs for these disorders. Furthermore, elucidating the relationship between DOHaD theory and NDDs will contribute to the popularization of preventive medicine [5].…”
Section: Introductionmentioning
confidence: 99%
“…They especially highlight the pragmatic dimension of the scientists' choices, as they are "compelled to make trade-offs or exchanges between competing priorities and commitments" (Ackerman et al, 2016, p. 197) in the name of objectivity, to make epidemiology more robust scientifically. Penkler et al also soundly document the discomfort of Developmental Origins of Health and Disease (DOHaD) researchers, who attempt to capture how environmental factors such as deprivation, nutrition, and stress shape individual and population health over the lifecourse (Penkler et al, 2022). While scientists are eager to develop more complex understandings of the environment in their daily practices, they are confronted with established methodological tools, disciplinary infrastructures, budgetary constraints and institutional contexts that favor a reductionist understanding of the environment and individualistic approaches toward health.…”
mentioning
confidence: 99%